ChemInform Abstract: 2, 4, 6‐Trichloro‐1, 3, 5‐triazine (TCT) Mediated One‐Pot Sequential Functionalization of Glycosides for the Generation of Orthogonally Protected Monosaccharide Building Blocks. Issue 1 (3rd January 2013) - Tatina, Madhubabu; Yousuf, Syed Khalid; Mukherjee, Debaraj
Abstract The advantages of the title reaction are a high regioselectivity, the use of a broad range of substrates and a mild, inexpensive, and nontoxic catalyst, functional‐group tolerance, mild reaction conditions, scalability (20 g), easy handling, and a wide application range.